A case of cicatricial alopecia associated with pemphigus: a case report - Roberto D'Astolto; Chiara Zangrando; Claudio Feliciani (Dermatology Reports, 2023)
Pemphigus is a chronic autoimmune bullous disease, associated with the production of autoantibodies directed against desmosomal proteins, such as desmogleins 1 and 3 (DSG1 and DSG3). Herein we present the case of an 83-year-old woman who referred to us with suspicious cicatricial alopecia of the scalp and a small, eroded lesion of the forehead, previously labeled as atrophic actinic keratosis after a skin biopsy. In our clinic, after a careful examination of the case, we decided to undergo two new skin biopsies of the scalp, in the suspicion of an inflammatory disease.